Adaptive model following tracking controller design for electrohydraulically position servomechanism - 420274 Muhammad Sufyan Basri (Skudai : Universiti Teknologi Malaysia, 2001)
Project Paper (Bachelor of Electrical Engineering) - Universiti Teknologi Malaysia, 2001